Culture of Litopenaeus vannamei of Brackish Water in Summer Season with Artificial Diet - Puli, Ratna Sekar; Birudu, Ravi Babu; Ravuru, Danya Babu; D, Darwin; Mude, Jagadish Naik (Asian Journal of Biological and Life Sciences, 2020)
The Pacific white shrimp is an Ecological important and Euryhaline species. The culture was conducted from 3 ponds each one of 0.7ha for the study. The Brackish water was selected in Chinaganjam Village, Prakasam District under Semi-Intesive culture system. In summer season in month of March to August, the water quality parameters were measured fortnightly in a month at 7a.m. The production was 8337, 8932 and 9450kg/120, 123 and 126 days and FCR was1.78, 1.81 and 1.82 for P1, P2 and P3. The artificial diet was provided 4 times/day with Manamei feed pellets (Protein 35 and 34%).The final growth was 27.7, 29.0 and 30.0g/120,123 and 126 days, respectively.
Keywords: Density; Feed; Growth and Production; L. vannamei; Salinity; Temperature